Toxicity and effect of whitening toothpastes on enamel surface - Rode, Sigmar de Mello [UNESP]; Sato, Tabata do Prado [UNESP]; Matos, Felipe de Souza; Correia, Ayla Macyelle de Oliveira [UNESP]; Camargo, Samira Esteves Afonso (My University, 2021)
This in vitro study evaluated the biocompatibility and abrasivity of whitening and conventional toothpastes. Samples of conventional (non-whitening) - Edel White Infant (EWI) - and whitening toothpastes - Edel White Whitening (EWW), Edel White CAREFORTE (EWC), Colgate Total 12 Ò Professional (C), and Oral-B Whitening (OB) - were dissolved in culture medium (0.2 g sample weight per mL). Human gingival fibroblasts (hGF) were placed in contact with different dilutions of culture media that had been previously exposed to these toothpastes. Cytotoxicity was then assessed using the methyl tetrazolium test (MTT) and the cell survival rate was determined. Genotoxicity was assessed by the micronucleus test (MNT) and the number of micronuclei was determined before and after exposure to the toothpaste solutions. The enamel surface roughness was evaluated in specimens of bovine teeth (n = 10 per group) before and after 10,000 brushing cycles, using the investigated toothpastes. The results were statistically analyzed using the Mann-Whitney U test and two-way ANOVA (p < 0.05). According to the MTT assay, EWW and OB presented significant cytotoxicity (p < 0.01), but no genotoxic (MNT) effects (p > 0.05). C toothpaste was statistically significantly abrasive to the enamel surface (p < 0.01). The findings of this study may be helpful for individualized selection of commercial toothpastes, as some whitening toothpastes present significant cytotoxicity and conventional toothpaste cause significant surface changes.